Measuring the Quality of MoRA's Education Services - Yarrow, Noah (World Bank, Jakarta, 2020)
We visited 350 primary schools and collected data from 1,838 teachers and 3,368 Grade 4 students to assess the quality of education service delivery in a nationally representative sample of schools of the Ministry of Religious Affairs and a smaller sample of schools of the Ministry of Education and Culture. We found that students were on average 1.5 years behind the learning level expected for 4th grade, representing a learning crisis. These low levels of learning were associated with high levels of teacher absence, low levels of availability of textbooks, and low levels of teacher subject knowledge and pedagogy skills but high levels of student satisfaction. We find higher levels of learning for students who have ever attended early childhood education, those who have eaten breakfast on the day of the assessment, as well as for female students. We offer some recommendations for addressing these challenges, drawing from schools with higher levels of student learning in the sample.